Coordinated movement of biomimetic dual PTZ visual system and wheeled mobile robot. Issue 6 (14th October 2014) - Xu, He; Xu, Yan; Fu, Hu; Xu, Yixian; Gao, X.Z.; Alipour, Khalil
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to explore a novel control approach for swift and accurate positioning and tracking of a mobile robot. Coordinated movement of the mobile robot-body and chameleon-inspired binocular "negative correlation" visual system (CIBNCVS) with neck has rarely been considered in conventional mobile robot design. However, it is vital in swift and accurate positioning and tracking of the target. Consequently, it is valuable to find an optimized method where the robot-body, the biomimetic eyes and neck could achieve optimal coordinated movement. Design/methodology/approach – Based on a wheeled mobile robot, a biomimetic dual Pan–Tilt–Zoom visual system with neck is constructed. The cameras can rely on the unique "negative correlation" mode of chameleon vision, and cooperate with neck, achieving swift search of the 160° scope in front of the robot. Genetic algorithm is used to obtain optimal rotation of the neck and robot-body. Variable resolution targeting is also applied for accurate aiming. Using these two approaches, we can achieve efficient targeting with low energy consumption. Particle filter algorithm is further utilized for real-time tracking. Findings – In the proposed approach, swift and accurate positioning and tracking of the target can be obtained. The rationality of the approach is verified by experiments on flat and sandy terrains with satisfactory results. Originality/value – This paper proposes a novel control approach for wheeled mobile robots, which achieves coordinated movement of the robot-body and CIBNCVS with neck concerning time and energy saving in the process of swift and accurate tracking.